Effects of hypertrophy training on spinal and corticospinal excitability within the quadriceps muscle group. - Restuccia, Joel (2018)
The current study was designed to examine corticospinal modulation during a 10-week hypertrophy-training program including a 6-week detraining period. Furthermore, the study aimed to explain the origins or corticospinal adaptation. We compared motor evoked potentials (MEPS) over the time period in the vastus lateralis muscle by employing a range of transcranial magnetic stimulation (TMS) techniques including the input/output curve (I/O curve), short intracortical inhibition (SICI), intracortical facilitation (ICF) and the silent period (SP) The main finding was that corticospinal excitability was reduced as the training protocol went on (P = 0.005) and then significantly rose after 3 weeks of detraining, followed by a reduction again after 6 weeks of detraining (P = 0.016). There were no significant differences found in short-intracortical inhibition (SICI), intracortical facilitation (ICF) and silent period (SP) (P > 0.05) or between bilateral and unilateral groups (P > 0.05) for all measurements. The current results support the idea that initially when exposed to training, the corticospinal tract of a target muscle becomes less excitable but also introduces the effects that detraining may play in response to corticospinal excitability.